The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1981-6723.04622
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological evaluation of feet-cutter disc for broiler with a self-washing system using heated and non-heated water

Abstract: Avaliação microbiológica de disco corta-pés de frangos com sistema de autolavagem utilizando água aquecida e não aquecida

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…(2023) 53 who reported a pH of 1.10 for black raspberries. Additionally, the present results showed higher acidity for red raspberries than that reported by de Souza et al (2014) 7 for red raspberries (1.86%) and lower than that reported by Cavani et al (2023) 54 (2.46%). These results showed that the increase in pH is proportional to the decrease in titratable acidity of raspberries, which can be attributed to climatic conditions and the ripening process of the fruit.…”
Section: Physicochemical Properties Of the Different Raspberry Samplescontrasting
confidence: 63%
“…(2023) 53 who reported a pH of 1.10 for black raspberries. Additionally, the present results showed higher acidity for red raspberries than that reported by de Souza et al (2014) 7 for red raspberries (1.86%) and lower than that reported by Cavani et al (2023) 54 (2.46%). These results showed that the increase in pH is proportional to the decrease in titratable acidity of raspberries, which can be attributed to climatic conditions and the ripening process of the fruit.…”
Section: Physicochemical Properties Of the Different Raspberry Samplescontrasting
confidence: 63%